Psychometric properties of the inventory of callous-unemotional traits short version (ICU-12) among detained female juvenile offenders and community youths - Pechorro, Pedro (Psychology, crime & law, 2017)
The presence of callous-unemotional (CU) traits delineates a subgroup of male youth with severe conduct problems and antisocial behavior. To date however, existing research into these features among females is markedly limited. Drawing on 377 female adolescents (103 selected from forensic settings and 274 selected from school settings) from Portugal, the current study is the first to simultaneously examine the psychometric properties of the 12-item shortened version of the Inventory of Callous-Unemotional Traits (ICU-12) in incarcerated and community female youth. Results provide support for the construct validity and reliability of the ICU-12 among this unique sample. Findings from this study also reveal evidence of convergent and discriminant validity with a number of theoretically relevant constructs (e.g. psychopathic features, aggression, and substance use). Clinical implications for using the ICU-12 with females are discussed.